Gender Norms and Household Labor: Time Use in the Context of Social Class Differentiation in Transitional China. (March 2022) - Zhang, Wei; Xu, Zhun
This paper studies the historical evolution of China's gender relations through the lens of housework time allocation. In particular, we highlight the role played by social class and income. Drawing upon data from the Chinese Health and Nutrition Survey, we find that during the period 1991–2011, being a peasant or earning less than the spouse was increasingly associated with a higher share of housework. The market process appears to have indirectly improved the social status of women (most likely rural women) married to peasant husbands as measured by the former's declining housework share. Such changes, however, have not challenged traditional patriarchal norms in the countryside and have even facilitated the rise of a new market-based patriarchy. Policy makers should empower women by tackling the different faces of patriarchy as a whole. JEL Classification: B51, J16, P16